Sodium butyrate enhances intestinal integrity, inhibits mast cell activation, inflammatory mediator production and JNK signaling pathway in weaned pigs. Issue 1 (January 2018) - Wang, Chun Chun; Wu, Huan; Lin, Fang Hui; Gong, Rong; Xie, Fei; Peng, Yan; Feng, Jie; Hu, Cai Hong
The present study aimed to investigate the effects of sodium butyrate on the intestinal barrier and mast cell activation, as well as inflammatory mediator production, and determine whether mitogen-activated protein kinase signaling pathways are involved in these processes. A total of 72 piglets, weaned at 28 ± 1 d age, were allotted to two dietary treatments (control vs. 450 mg/kg sodium butyrate) for 2 wk. The results showed that supplemental sodium butyrate increased daily gain, improved intestinal morphology, as indicated by greater villus height and villus height:crypt depth ratio, and intestinal barrier function reflected by increased transepithelial electrical resistance and decreased paracellular flux of dextran (4 kDa). Moreover, sodium butyrate reduced the percentage of degranulated mast cells and its inflammatory mediator content (histamine, tryptase, TNF-α and IL-6) in the jejunum mucosa. Sodium butyrate also decreased the expression of mast cell-specific tryptase, TNF-α and IL-6 mRNA. Sodium butyrate significantly decreased the phosphorylated ratio of JNK whereas not affecting the phosphorylated ratios of ERK and p38. The results indicated that the protective effects of sodium butyrate on intestinal integrity were closely related to inhibition of mast cell activation and inflammatory mediator production, and that the JNK signaling pathway was likely involved in this process.